PENERAPAN PSAK NO. 46 DALAM AKUNTANSI PAJAK UNTUK MENINGKATKAN KEPATUHAN PELAPORAN SPT TAHUNAN - Sinaga, Debora Winda; Tikasari, Nopi (Universitas Prof. Dr. Moestopo (Beragama), 2025)
ABSTRACT This study aims to evaluate the impact of the implementation of PSAK No. 46 on tax accounting practices at PT Bank Rakyat Indonesia (BRI) and how its application influences compliance with Annual Tax Return (SPT) reporting. PSAK No. 46 regulates the recognition of income tax and provides guidance for companies to manage tax obligations more efficiently. This research uses a qualitative case study approach by analyzing BRI’s financial statements from 2021 to 2023. The results show that the application of PSAK No. 46 contributes to improving transparency and accuracy in tax reporting, leading to better tax compliance. The increase in Deferred Tax Assets, Income Tax Expense, and higher Tax Payments in 2023 reflects the company’s efficiency and compliance with tax regulations. This study also highlights the challenges faced by companies in implementing PSAK No. 46, and how digital technology can enhance the effectiveness of tax reporting. Based on these findings, this study recommends that companies strengthen training related to PSAK No. 46 and utilize technology in the taxation process to support better tax compliance in the future.Keywords: Tax Accounting, PSAK No. 46, Deferred Tax Assets, Tax Compliance, Annual Tax Return.